Some Biomechanical Limitation During Acceleration Phase and Its Relationship With (110) m Hurdles Achievement for Advance Runners - Subhi, Dheyaa; Najah, Yaseer (Journal of Physical Education, 2022)
The importance of the research lies in specifying the percentage of biomechanical limitation during acceleration phase in 110 hurdles for advance hurdlers. The researchers noticed that achievement is not good thus the research aimed at identifying the relationship between biomechanical limitations and 110 m running during acceleration phase as well as identifying percentage of these limitations on achievement.  The researcher used the descriptive method on (8) hurdlers then finally they recommended the necessity of paying attention to physical training and developing physical abilities that this event require as well as selecting hurdlers according to anthropometric measurements. The researchers recommended making similar studies on other variables and making sure coaches during hurdlers training to develop achievement.